IMPLEMENTATION OF QUALITY FUNCTION DEPLOYMENT ANALYSIS BY ADOPTING IN SERVICE QUALITY METHODS EFFORTS TO IMPROVE SERVICE QUALITY AT UPT. RUMAH SAKIT KHUSUS MATA IN NORTH SUMATRA PROVINCE - Aris Handiyoko Sibuea; Endang Sulistya Rini; Linda Trimurni Maas (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
UPT. Rumah Sakit Khusus Mata Provinsi Sumatera Utara is one of the type B eye hospitals that serves as a referral hospital for eye disease treatment. Based on the community satisfaction index in 2022, there were 2 service elements below standard value according to regulation no.14 of 2017 issued by the Ministry of Administrative Reform and Bureaucratif Reform. These service elements are service time and executor competence. This research aims to identify the service quality of these 2 unsatisfactory elements using the service quality methode and quality function deployment on patients of the UPT. Rumah Sakit Khusus Mata Provinsi Sumatera Utara. The research begins by describing the 2 service elements into service quality dimensions, resulting in 17 attributes from 5 dimensions. The overall gap analysis reveal negative gaps, and the House of Quality concludes that special attention should be given to the technical response, which has an above-average score 111,5 in its development. This ensures that the service attributes receive good ratings in the future.